New onset acute symptomatic seizure and risk factors in coronavirus disease 2019: A retrospective multicenter study. (2nd May 2020) - Lu, Lu; Xiong, Weixi; Liu, Dan; Liu, Jing; Yang, Dan; Li, Nian; Mu, Jie; Guo, Jian; Li, Weimin; Wang, Gang; Gao, Hui; Zhang, Yingying; et al.
Abstract: Our aim was to clarify the incidence and risk of acute symptomatic seizures in people with coronavirus disease 2019 (COVID‐19). This multicenter retrospective study enrolled people with COVID‐19 from January 18 to February 18, 2020 at 42 government‐designated hospitals in Hubei province, the epicenter of the epidemic in China; Sichuan province; and Chongqing municipality. Data were collected from medical records by 11 neurologists using a standard case report form. A total of 304 people were enrolled, of whom 108 had a severe condition. None in this cohort had a known history of epilepsy. Neither acute symptomatic seizures nor status epilepticus was observed. Two people had seizurelike symptoms during hospitalization due to acute stress reaction and hypocalcemia, and 84 (27%) had brain insults or metabolic imbalances during the disease course known to increase the risk of seizures. There was no evidence suggesting an additional risk of acute symptomatic seizures in people with COVID‐19. Neither the virus nor potential risk factors for seizures seem to be significant risks for the occurrence of acute symptomatic seizures in COVID‐19.